Determinants of corporate performance: empirical study on fashion smes in depok city - HS, Ikhwan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The Depok City government provides full support to MSMEs in Depok City in order to expand their reach with the expansion of market access. The success of a business can be seen through the performance of the business. This study aims to determine the effect of human competence and supply chain management on competitive advantage and its impact on corporate performance in Fashion SMEs in Depok City. The sample used in this study was 150 respondents of micro, small and medium business owners in the Depok City area with purposive sampling technique. This study uses data analysis with the SEM-Partial Least Square (PLS) approach in the form of the Smart-PLS version 3.0 application. The results of this study indicate human competence and supply chain management on corporate performance mediated by competitive advantage. This research is limited to MSME players in Depok City, so it cannot represent the performance of MSMEs as a whole. By effectively managing and utilizing these advantages, MSMEs can achieve sustainable growth and success. Thus human resource competencies and supply chain management will be able to improve the competitiveness of the company.